AFCPOA-based optimal dispatch of hybrid PV-wind DGs for voltage stability and loss reduction in radial distribution network - Sunil Ankeshwarapu (Next Energy)
This study proposes the Adaptive Fuzzy Campus Placement-based Optimization Algorithm (AFCPOA) for optimal dispatch of Renewable Distributed Generators (RDGs) — Solar PV, Wind, and Hybrid (PV+Wind) in a Radial Distribution Network (RDN) considering dynamic hourly and seasonal load variations. AFCPOA minimizes total power losses and enhances voltage stability using a Network Topology-based Load Flow approach. Its performance was evaluated on the IEEE 33-bus system and benchmarked against Hybrid Genetic Algorithm (GA)-Jaya, Jaya Algorithm, Shuffled Frog-Leaping Algorithm (SFLA), Particle Swarm Optimization (PSO), and GA. Results show that AFCPOA achieved a 42.6% reduction in total losses compared to the base case and outperformed other algorithms by 9–18% in loss reduction, with an average voltage profile improvement of 5.3%. These findings demonstrate AFCPOA’s superior ability to handle seasonal load variability and optimize RDG integration efficiently.